Firm’s Value: Governance, Risk Management, Compliance (GRC) and Profitability - Muhamad Muslih; Nurlina (Universitas Muhammadiyah Surakarta, 2024)
The research being conducted investigates the effect of governance, risk management, compliance (GRC), and profitability on the value of firms. The audit committee, managerial ownership, institutional ownership, and independent board of commissioners represent the corporate governance variables applied in this study. The research population covers firms in the basic materials sector listed on the Indonesia Stock Exchange between 2019 and 2022. The sampling technique employed is purposive sampling, consisting of a sample size of 15 enterprises observed over four years. The testing methodology employed is panel data regression using Eviews. The findings indicate that business value is influenced by corporate governance, risk management, compliance (GRC), and profitability simultaneously. Partial testing suggests that the audit committee, independent board of commissioners, risk management, and compliance positively affect the firm's value. On the contrary, both managerial ownership and institutional ownership have adverse effects, but profitability does not affect the firm's value.